The effects of various boron compounds on the thermal, microstructural and mechanical properties of PLA biocomposites - Avci, Ali; Eker, Aysegul Akdogan; Bodur, Mehmet Safa; Kucukyildirim, Bedri Onur (ELSEVIER, 2024)
This study aims to understand how ulexite, boric acid-borax mixtures (1:1), and zinc borate fillers affect the thermal and mechanical properties of the poly (lactic acid) (PLA). For this purpose, three different boron fillers were added to the PLA matrix at four different concentrations of 3 %, 5 %, 8 %, and 12% wt. UL-94 test was conducted to comprehend the impacts of boron fillers on the fire resistance of the biocomposites. Thermogravimetric analysis was applied to determine the thermal stability, mass loss, and decomposition temperature of the samples. The biocomposite's significant mechanical properties, such as tensile strength, flexural strength, Young's modulus, and elongation at break, were assessed using tensile and three-point bending tests. Although the tensile and flexural strengths of PLA reduced, flexural and Young's modulus rose by roughly 20 % and 22 %, respectively, with rising boron filler rates.
Keywords: Biocomposite; Flame retardancy; Mechanical properties; Injection moulding; FLAME-RETARDANT; ZINC BORATE; WOOD FLOUR; ACID; MORPHOLOGY; FIRE; FLAMMABILITY; Thermodynamics; Chemistry